KELANGSUNGAN DAN PERUBAHAN TARI SEDULANG SETUDUNG KABUPATEN BANYUASIN - Rian Ardiansyah; Dwiyasmono Dwiyasmono (Institut Seni Indonesia Surakarta, 2020)
Since this dance was created in 2002 it already go through some developments and still on going until now. The purpose of this research is to uncover about the causative factors of Setulang Setudung dance continuity and changes in Banyuasin District. This research is using a qualitative kind of research. The process of the data collection has involve observations, interviews and documentations. The results of this research showing the present form of Setulan Setudung dance which is including moves, musics, costume and make up, also properties. Beside that, the results of this research is that Setulan Setudung dance still on goin until now and already going through cange because of the art response against the existing challenges such as the impact of oustiders culture, government, economy and education. Keywords: Sedulang Setudung dance, continuity, and Dance Change.